Young people in a pandemic: from frustration to drug use - Pérez García, Rubén Gregorio; Agrela Romero, Belén (Cuadernos de Trabajo Social, 2023)
The aim of this work is to show some of the psychosocial effects on young people in Spain in the context of a pandemic, analyzing their experiences of lockdown and the links established between stress, frustration and drug use. We explore potential changes in consumption patterns through a quantitative and qualitative analysis carried out with young people living in Andalusia between March and June 2020. From a social work perspective, the aim is to use the results of this research to understand how regularly young people are using drugs, the factors associated with starting drug use and the effects of these substances during lockdown. The association between coping and drug use indicated a psychosocial vulnerability among the young population.